IDENTIFICATION OF CLASTIC LIMESTONE CHARACTERISTICS AS A BUILDING MATERIAL IN SURADE AREA, WEST JAVA, INDONESIA - Wahidah, Andhika Nurul; Fachrudin, Kurnia Arfiansyah; Ikhram, Rinaldi (Faculty of Geological Engineering, Universitas Padjadjaran, 2017)
Surade subdistrict is located in Sukabumi District, West Java with an area of 364.19 km² which is about 60% lithology of this area is in the form of clastic rock of Cibodas Formation. Surade Subdsitrict is also included in Geopark Ciletuh-Palabuhanratu area. As a quarry material, limestones are beneficial in the interests of industry and building materials. Locals use limestone for construction material as a bricks. Material are dig in small scale for both individual and large-scale use fo resale. Material mined manually by sawing a massive limestone according to a certain size. Macroscopically, this limestone has a yellow color, allochtonous type, calcarenite grain size, open fabric, good sorting, exposed with massive or parallel laminate structures with a thick outcrop up to 7 meters. Microscopically, the type of limestones is packstone and wackestone locally. Composed of shell and non-shell fragments in the form of rock fragments, as well as other mineral fragments. Limestone has been dissolved and visible cementation of the found voids. Limestone is not too good as a substitute for bricks in the building construction because it has low value of compressive strength that will affect the resistance of the building’s burden. This limestone is easily soluble and less resistant to the weather so it can reduce the quality of building, but has the advantage to store more water vapor it is good to regulate humidity in tropical buildings. The existence of clastic limestone becomes the potential of geological diversity in Geopark Ciletuh-Palabuhanratu area. Locals take this advantage to boost the economy, but needs sepecial attention to watching of mining activities to avoid adverse affect at conservation area.Keywords: clastic limestone, Surade, Indonesia, building materials, Ciletuh-Palabuhanratu Geopark